2011
DOI: 10.1038/nn.2777
|View full text |Cite
|
Sign up to set email alerts
|

A neuroprotective role for polyamines in a Xenopus tadpole model of epilepsy

Abstract: Polyamines are endogenous molecules involved in cell damage following neurological insults, although it is unclear whether polyamines reduce or exacerbate this damage. We used a developmental seizure model in which we exposed Xenopus laevis tadpoles to pentylenetetrazole (PTZ), a known convulsant. We found that, after an initial PTZ exposure, seizure onset times were delayed in response to a second PTZ exposure 4 h later. This protective effect was a result of activity-dependent increases in synthesis of putre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 47 publications
1
43
0
1
Order By: Relevance
“…In a recent study by Bell et al (Bell et al, 2011) involving a protocol consisting of two consecutive PTZ-induced seizures and a combination of behavioral, electrophysiological and pharmacological experiments, it was shown that the first initial PTZ-induced seizure in a tadpole increases the production of polyamines [an observation that had also been reported in a rodent seizure model (Hayashi et al, 1993)]. Elevated polyamine levels were found to boost the production and release of the inhibitory transmitter GABA, which rendered tadpoles less prone to future seizures.…”
Section: A Tadpole Model For Epileptic Seizurementioning
confidence: 94%
See 2 more Smart Citations
“…In a recent study by Bell et al (Bell et al, 2011) involving a protocol consisting of two consecutive PTZ-induced seizures and a combination of behavioral, electrophysiological and pharmacological experiments, it was shown that the first initial PTZ-induced seizure in a tadpole increases the production of polyamines [an observation that had also been reported in a rodent seizure model (Hayashi et al, 1993)]. Elevated polyamine levels were found to boost the production and release of the inhibitory transmitter GABA, which rendered tadpoles less prone to future seizures.…”
Section: A Tadpole Model For Epileptic Seizurementioning
confidence: 94%
“…A protocol to reliably induce controlled seizures in the Xenopus tadpole has been developed (Hewapathirane et al, 2008) and has already led to a fundamental insight into how endogenous polyamines can play a neuroprotective role in response to an epileptic seizure (Bell et al, 2011). …”
Section: A Tadpole Model For Epileptic Seizurementioning
confidence: 99%
See 1 more Smart Citation
“…GABA production through this alternative evolutionarily conserved pathway also exists in Xenopus tadpole (15) and mammalian cells (1619). Glial cells can also utilize putrescine to produce GABA during retinal early development (18, 20).…”
mentioning
confidence: 99%
“…It is produced naturally by the decarboxylation of ornithine and serves as a biosynthetic precursor to both spermine and spermidine. Even after decades of intense research, new biological functions continue to be routinely discovered for putrescine (Bell et al, 2011).…”
Section: Resultsmentioning
confidence: 99%